Bright fluorescent purine analogues as promising probes. (1st December 2021) - He, Xin; Kuang, Shuang; Gao, Qian; Xie, YuXin; Ming, Xin
Abstract: Modified bright fluorescent nucleosides that respond to the microenvironment have great potential as probes. A series of novel 8-(phenylethynyl)phenylated 2-amino-2′-deoxyadenosine and 2′-deoxyisoguanosine derivatives have been synthesized by Sonogashira-type coupling reaction and Suzuki reaction. The maximum emission of the new compounds is in the visible region, with strong solvatochromicity and pH-dependent fluorescent properties. Furthermore, some of them exhibit bright fluorescence emissions in various solvents (ε × Φ = 4000–39, 000 cm −1 M −1 ). These consequences indicate that purine analogues could respond to the microenvironment and serve as promising fluorescent probes. Supplemental data for this article is available online at https://doi.org/10.1080/15257770.2021.2004418 .